Enhancing employability skills through industrial training programme - Yusoff Y.M.; Omar M.Z.; Zaharim A.; Mohamed A.; Muhamad N.; Mustapha R. (2023)
Employers nowadays consider a graduate's academic achievement alone is not sufficient for hiring the engineering graduates. They sometimes find achievement other than academic such as employability skills to be important in the recruitment process. Hence, the purpose of this study is to examine the employers' perceptions on the performance of graduates and interns as an effort from Faculty of Engineering and Building Environment of Universiti Kebangsaan Malaysia (UKM) to meet the job market demands. Two different sets of questionnaires were used to collect data. First, data collected on the employers' perceptions on skills possessed by new engineers in their workforce from a sample of 302 employers of engineering graduates in Klang Valley. Second, data collected on assessment of the performance of engineering industrial training students from 305 employers of interns. The study reveals that attributes exposed in industrial training programme fulfil the attributes required by employers. It shows that the industrial training programme is an essential component of engineering curricula. The programme develops undergraduates' employability skills through activities that gave the interns an exposure to industry practices. The industrial training also strengthens employability skills of engineering students through relevant work experience. The similar trend on percentage of agreement by employers also indicates that the attributes attained by UKM's students in industrial training meet the criteria required by employers.